STABILITY OF OMEGA-3 COMPOUNDS COMPLEX WITH PPAR-γ RECEPTOR AS AN ANTI-OBESITY USING MOLECULAR DYNAMIC SIMULATION - MUSFIROH, IDA; MEGAWATI, GINNA; HERAWATI, DEWI M. D.; IFAYA, MUS (International Journal of Applied Pharmaceutics, 2022)
Objective: Obesity is a major contributor to comorbid diseases based on low grade chronic inflammation. Omega-3 fatty acids have a role in inflammation so it is thought to prevent obesity. This study was conducted to analyze the stability of omega-3 fatty acids with the PPAR-γ receptor using molecular dynamic simulation to investigate the relationship of macromolecule interactions to biologically relevant as an obesity comorbid. Methods: The methods consisted of ligand acquisition, molecular dynamic simulation, and analysis of dynamic molecular results using Gromacs 2016.3 software and the results of the MD analysis were carried out by simulating time with VMD software and graphing the results of MD data analysis using Microsoft Excel. Results: The result showed that docosahexaenoic acid (DHA), docosapentaenoic acid (DPA), and heneicosapentaenoic acid (HPA) have good stability. Average RMSD values of DHA, DPA, and HPA were 0.347 Å, 0.464 Å, and 0.706 Å with similar pattern of fluctuation across the region. DHA forms a hydrogen bond to Tyr347 and Leu343. Meanwhile, DPA binds to Asn52 and HPA bind to Arg213. DHA, DPA, and HPA have an average SASA of 233.91 nm2, 231.47 nm2, and 225.52 nm2, respectively. DHA has the lowest total binding energy (-129.914 kJ/mol) compared to DPA (-102.018 kJ/mol) and HPA (-115.992 kJ/mol). Conclusion: Based on the molecular dynamics simulation approach, omega-3 compounds, DHA, DPA, and HPA showed that DHA has good stability compared to DPA and HPA. DHA, DPA, and HPA can be used as lead drugs to bind to PPAR-γ receptors to prevent and treat obesity.